The Impact of Promotion Strategies in GoFood Platform to Customer Decision: Case Study of Eatzy Indonesia - Dakhilullah, Hafizh Ahmad; Qastharin, Annisa Rahmani (Proceedings International Conference on Education Innovation and Social Science, 2023)
The growth of internet users in Indonesia is increasing from year to year, almost half of the Indonesian population are internet users. With this data, many entrepreneurs are adapting to existing developments by carrying out their business activities or selling by utilizing developing technology, especially the internet or what we often refer to as online activities. From the data obtained, Indonesia has a high transaction value for the online food industry which reaches 78.4 trillion rupiah. There are 3 major players in the online food industry in Indonesia, and GoFood is one of the largest online food delivery platforms in Indonesia that has many users. Eatzy Indonesia as a company engaged in the food industry wants to expand its sales channels to online means. Seeing the potential, Eatzy Indonesia partnered with GoFood to sell its retail food products through the platform. As a new partner of GoFood, Eatzy Indonesia needs to know effective ways to get sales, one of which is by utilizing the promotional features provided by GoFood. Therefore, this study aims to analyze the effect of promotional strategies on customer decisions for GoFood's new partner, Eatzy Indonesia. This study will analyze 144 respondents using quantitative methods with Multiple Linear Regression as a data processing method using SPSS software. The result is that the promotional strategies provided by GoFood (GoFood Search Ads, GoFood Category Ads, and GoFood Menu Discounts) have a positive influence on customer decisions.